Peculiarities of crystal structures and photophysical properties of GaIII/LnIII metallacrowns with a non-planar [12-MC-4] core. Issue 7 (2nd March 2020) - Nguyen, Tu N.; Eliseeva, Svetlana V.; Chow, Chun Y.; Kampf, Jeff W.; Petoud, Stéphane; Pecoraro, Vincent L.
Abstract : The direct synthetic approach can be used to create a series of visible and near-infrared emitting Ga III /Ln III metallacrowns with a non-planar [12-MC-4] core. Abstract : A new series of gallium(iii )/lanthanide(iii ) metallacrown (MC) complexes (Ln-1 ) was synthesized by the direct reaction of salicylhydroxamic acid (H3 shi) with Ga III and Ln III nitrates in a CH3 OH/pyridine mixture. X-ray single crystal analysis revealed two types of structures depending on whether the nitrate counterion coordinate or not to the Ln III : [LnGa4 (shi)4 (H2 shi)2 (py)4 (NO3 )](py)2 (Ln = Gd III, Tb III, Dy III, Ho III ) and [LnGa4 (shi)4 (H2 shi)2 (py)5 ](NO3 )(py) (Ln = Er III, Tm III, Yb III ). The representative Tb-1 and Yb-1 MCs consist of a Tb/YbGa4 core with four [Ga III –N–O] repeating units forming a non-planar ring that coordinates the central Ln III through the oxygen atoms of the four shi 3− groups. Two H2 shi − groups bridge the Ln III to the Ga III ring ions. The Yb III in Yb-1 is eight-coordinated while the ligation of the nine-coordinated Tb III in Tb-1 is completed by one chelating nitrate ion. Ln-1 complexes in the solid state showed characteristic sharp f–f transitions in the visible (Tb, Dy) and near-infrared (Dy, Ho, Er, Yb) spectral ranges upon excitation into the ligand-centered electronic levels at 350 nm. Observed luminescence lifetimes and absolute quantum yields were collected and discussed. For Yb-1, luminescence data were also acquired in CH3 OH and CD3 OD solutions and a more extensive analysis of photophysical properties was performed. This work demonstrates that while obtaining highly luminescent lanthanide(iii ) MCs via a direct synthesis is feasible, many factors such as molar absorptivities, triplet state energies, non-radiative deactivations through vibronic coupling with overtones of O–H, N–H, and C–H oscillators and crystal packing will strongly contribute to the luminescent properties and should be carefully considered.